STUDI KASUS: PENATALAKSANAAN TERAPI KOMPRES HANGAT AIR JAHE MERAH TERHADAP TINGKAT NYERI PADA PASIEN DENGAN ASAM URAT - Kurnia, Karina; Andriyani, Septian; Sulastri, Afianti; Suparto, Tirta Adikusuma (Yayasan Healing and Healthcare Education, 2024)
Gout is a degenerative problem that attacks the joints and is caused by complications of hyperuricemia. One therapy to reduce pain is a warm compress with red ginger water. Red ginger is bitter, spicy and also anti-inflammatory so it can reduce joint pain. This study aims to describe the management of warm compress therapy with red ginger water for pain in subjects with gout. This research used a qualitative research design with a case study approach in the Cikole Community Health Center Work Area, West Bandung Regency from March 29-April 4 2024, with two subjects who experienced gout, who were experiencing moderate pain (scale 1-6). The intervention was carried out for seven consecutive days with a duration of 15 minutes in the afternoon at each patient's home. Pain level assessment was measured using the Numerical Rating Scale (NRS). This research shows that a warm compress with red ginger water can reduce moderate pain to mild pain. The reduction in pain is due to the effect of the active substance content in red ginger which is able to inhibit the formation of prostaglandins and leukotrienes which can transmit impulses to the brain to block painful stimuli, so that pain impulses to the brain will be reduced and pain will decrease. Therefore, it is recommended to provide warm compress therapy with red ginger water to patients suffering from gout.